2020
DOI: 10.1186/s13018-020-01654-1
|View full text |Cite
|
Sign up to set email alerts
|

The OLIF working corridor based on magnetic resonance imaging: a retrospective research

Abstract: Objective: To provide an anatomical basis for the development of oblique lumbar interbody fusion (OLIF) in Chinese patients. Methods: Between November 2018 and June 2019, 300 patients' lumbar MRI data were reviewed. According to the Moro system and zone method described by us, the axial view was vertically divided into 6 zones (A, I II, III, IV, P) and was horizontally divided into 4 zones (R, a, b, c, L). The locations of left psoas muscle and the major artery at L2/3, L3/4, and L4/5 levels were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…Then, a surgical incision of 4–6 cm and 3–5 cm ventral to the anterior vertebral cortex of the target intervertebral disc was made. We used blunt dissection of abdominal external oblique, internal oblique, and transversalis muscles to approach the retroperitoneal space and the disc space in the oblique corridor (the space between the major blood vessel and the psoas muscle) 14 . After the target disc space was identified, sequential soft tissue dilators and blade retractor were applied to establish the retroperitoneal pathway to the oblique corridor under direct visualization.…”
Section: Methodsmentioning
confidence: 99%
“…Then, a surgical incision of 4–6 cm and 3–5 cm ventral to the anterior vertebral cortex of the target intervertebral disc was made. We used blunt dissection of abdominal external oblique, internal oblique, and transversalis muscles to approach the retroperitoneal space and the disc space in the oblique corridor (the space between the major blood vessel and the psoas muscle) 14 . After the target disc space was identified, sequential soft tissue dilators and blade retractor were applied to establish the retroperitoneal pathway to the oblique corridor under direct visualization.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the authors highlighted certain anatomic relationships of psoas-vessels at L4–L5 being nonconducive for a safe of OLIF technique (Figure 7). 15,16 Contrastingly, we found that a left-sided ATP approach provided an average operative window of 36 mm consistently allowing for safe surgery (n=4 AL zone patients. Figure 7).…”
Section: Discussionmentioning
confidence: 63%
“…To make the procedure as safe as possible, several image-based and cadaveric dissection studies have intensively examined the surgical ATP corridor [7][8][9][10][11][12][13][14][15][16][17]. Most of these publications are based on Asian [8][9][10][11][12][13][14]16] and American [7,15,17] populations.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the location of these structures can obstruct or modify the surgical corridor to reach the disc, thereby increasing the risk of fatal intraoperative vascular complications [8]. Therefore, anatomical research based on different imaging modalities and cadaveric studies has detailed the features of the left-sided ATP oblique corridor and the surrounding spinal retroperitoneal structures [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%